SISTEM INFORMASI PENGENDALIAN BAHAN BAKU MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING PADA PD. SAMIJAYA SUKABUMI BERBASIS WEB - RISHMAYA, RIVA LADY (Jurnal Sistem Komputer, 2020)
A Company often has difficulties in controlling raw materials, including too much or too little supply. This study aims to control or know the amount of raw material that must be provided, while the formulation of the problem of this study is how to apply the Material Requirement Planning method to control the amount of raw material stock, how the system design is made, and how the system interface is made. The basic theory used is management information systems, supply chain management and Material Requirement Planning. Where the theory is related to research conducted. The research sample was carried out by direct interviews with company owners.